Laser scribed graphene for supercapacitors - Zhengfen Wan (Institue of Optics and Electronics, Chinese Academy of Sciences, 2021)
Supercapacitors, with the merits of both capacitors for safe and fast charge and batteries for high energy storage have drawn tremendous attention. Recently, laser scribed graphene has been increasingly studied for supercapacitor applications due to its unique properties, such as flexible fabrication, large surface area and high electrical conductivity. With the laser direct writing process, graphene can be directly fabricated and patterned as the supercapacitor electrodes. In this review, facile laser direct writing methods for graphene were firstly summarized. Various precursors, mainly graphene oxide and polyimide were employed for laser scribed graphene and the modifications of graphene properties were also discussed. This laser scribed graphene was applied for electrochemical double-layer capacitors, pseudo-capacitors and hybrid supercapacitors. Diverse strategies including doping, composite materials and pattern design were utilized to enhance the electrochemical performances of supercapacitors. Featured supercapacitors with excellent flexible, ultrafine-structured and integrated functions were also reviewed.